Cardiovascular adverse effects associated with the use of anti-HER2 in breast cancer treatment - Valente, Patricia Marques Soares; da Silva, Paula Nogueira; da Silva, Licínio Esmeraldo; Martins, Wolney de Andrade; de Castilho, Selma Rodrigues (Frontiers in Pharmacology, 2023)
Background: Cancer represents an important public health problem with increasing incidence, prevalence, and mortality, affecting the entire Western population, especially in developed and developing countries. The use of monoclonal antibodies has revolutionized the treatment of cancer, but this treatment can cause adverse cardiovascular effects (AE). Objective: The objective of this paper is to identify and classify AE in breast cancer patients in the use of Trastuzumab in two health institutions. Methods: Retrospective study of medical records of patients with breast cancer Her 2+ submitted the therapy with trastuzumab in early and advanced stage of the disease. Review conducted in a university hospital and a private clinic, both located in Rio de Janeiro State, Brazil. Results: Cardiovascular events were late for trastuzumab, with predominance of moderate reactions. There was a predominance of dyspnea, increased blood pressure, fatigue and reduced left ventricular ejection.The results resemble similarities in the pattern of the institutions' reactions. Identify possible AE and know the toxicity profile of trastuzumab can contribute to a safer therapy.